Dritter Beitrag zur Kenntnis der Tineiden von Afghanistan (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1973)
The present paper contains the evaluation of the Tineidae collected in various parts of Afghanistan by Mrs. E. Vartian and Dr. F. Kasy (Vienna) in 1962, 1963, 1965 and 1969 and by Dr. H. G. Amsel (Karlsruhe) in 1966. Eleven new species and one new subspecies are described. This increases the number of species known from Afghanistan from 25 to 42.Nomenclatural Actsorientale Petersen, 1973 (Ateliotum petrinellum), sspec. n.paghmanella Petersen, 1973 (Episcardia), spec. n.splendens Petersen, 1973 (Episcardia), spec. n.grisea Petersen, 1973 (Infurcitinea), spec. n.obscura Petersen, 1973 (Infurcitinea), spec. n.safedella Petersen, 1973 (Infurcitinea), spec. n.barikotellus Petersen, 1973 (Nemapogon), spec. n.egregiellum Petersen, 1973 (Obesoceras), spec. n.subtile Petersen, 1973 (Obesoceras), spec. n.nana Petersen, 1973 (Paratinea), spec. n.trimaculata Petersen, 1973 (Paratinea), spec. n.semifulvelloides Petersen, 1973 (Tinea), spec. n.